Efforts in the Formation and Development of Nuclear Medicine in Vietnam - Mai, Trong Khoa (Nucl Med Mol Imaging, 2019)
The foundations of nuclear medicine in Vietnam were established from 1970. Until now, after 48 years of development, in Vietnam, we have some basic equipment including 31 SPECT, 4 SPECT/CT machines, 11 PET/CT scanners, five cyclotrons, and one nuclear reactor. Many nuclear medicine techniques in diagnosis and treatment have been routinely performed at provincial and central level health facilities such as tumor scintigraphy, thyroid scintigraphy, bone scintigraphy, kidney scintigraphy, cardiac scintigraphy, and radio-isotope therapy with I-131 and P-32. Selective internal radiation therapy with Y-90 microsphere and I-125 radioactive seed implantation has been also successfully applied in some big hospitals. However, there are still many difficulties for Vietnam as the lack of new widely used radioisotopes such as Ga-67, Cu-64, Samarium-153, and Lutetium-177 and the lack of nuclear medicine specialists. In the future, we are putting our efforts on the applications of new isotopes in diagnosis and treatment of cancers (theranostic) like Ga-68-DOTATATE, Lutetium-177-DOTATATE, Ga-68-PSMA, and Lutetium-177-PSMA, equipping modern nuclear medicine diagnostic tools, strengthening the human resources training in nuclear medicine. At the same time, we are trying our best to strengthen the cooperation with international nuclear medicine societies in over the world.